Kerangka Etis Artificial Intelligence dalam Pendidikan Islam: Mengintegrasikan Maqasid Syariah di Era Pembelajaran Digital - Fathorrozy; Naidatus Syarifah; Khairul Anam; Nurul Qomariyah (Islamic Education Management Study Program, Tarbiyah and Teacher Training Faculty, State Islamic University of Madura, 2026)
The rapid development of artificial intelligence has significantly transformed educational practices, including teaching, learning, and academic management. AI-based technologies such as intelligent tutoring systems, automated assessment, and generative AI applications provide new opportunities to enhance learning efficiency and accessibility. Nevertheless, the increasing adoption of artificial intelligence in education also brings a number of ethical concerns, including issues related to academic integrity, risks to data privacy, algorithmic bias, and the possible weakening of students’ critical thinking skills. Within the sphere of Islamic education, these concerns underline the importance of establishing an ethical framework that harmonizes technological advancement with Islamic moral principles. Therefore, this study seeks to formulate an ethical framework for the application of artificial intelligence in Islamic education by integrating the principles of Maqasid Shariah with contemporary digital learning practices. This research applies a qualitative conceptual approach through a literature review and thematic analysis.The findings suggest that the principles of Maqasid Shariah can serve as an ethical foundation for AI use in education, particularly in protecting intellect, religion, human dignity, and academic integrity. This framework is expected to guide Islamic educational institutions in integrating AI technologies responsibly.